Synthesis and biological evaluation of new piplartine analogues as potent aldose reductase inhibitors (ARIs) - Ramasubba Rao, Vidadala (2012)
As a continuation of our efforts directed towards the development of anti-diabetic agents from natural sources, piplartine was isolated from Piper chaba, and was found to inhibit recombinant human ALR2 with an IC50 of 160 µM. To improve the efficacy, a series of analogues have been synthesized by modification of the styryl/aromatic and heterocyclic ring functionalities of this natural product lead. All the derivatives were tested for their ALR2 inhibitory activity, and results indicated that adducts 3c, 3e and 2j prepared by the Michael addition of piplartine with indole derivatives displayed potent ARI activity, while the other compounds displayed varying degrees of inhibition. The active compounds were also capable of preventing sorbitol accumulation in human red blood cells.